Building Learning Experiences: The Transformative Power of Constructionist Makerspaces in Holistic Child Development (Constructionism Conference Proceedings, 2025)
This case study explores the educational potential of a constructivist makerspace, analyzing its impact on a child’s development across multiple dimensions: cognitive, creative, and intrapersonal competencies. Through engaging with analog and digital tools, the child advanced from basic problem-solving tasks to complex projects requiring conceptual understanding and technological integration. The findings highlight how iterative design processes, guided by constructivist principles, foster critical thinking, creativity, and learning autonomy. Although the single-case design limits more general applications, the study offers practical insights into strategies that enhance engagement and holistic skill development in student-centered learning environments like educational makerspaces.